¡Múdate ya! - Baca Grández, Micaela Lucía (Pontificia Universidad Católica del Perú, 2025)
The artistic research project ¡Múdate ya! aims to question the development of architecture based on the market; analyze how the languages and aesthetics of real estate marketing reinforce hegemonic aspirational narratives; explore the organic emotional connections in a home built for its inhabitants; and denormalize the trend toward downsizing and standardization of housing in Metropolitan Lima. The materials used include thread and tracing paper, while the methods encompass drawing with machine stitching on paper and the comparison of case studies. The research is guided by the following question: does our way of living determine architecture, or does architecture determine our way of living?.

El proyecto de investigación artística ¡Múdate ya! tiene como objetivo cuestionar el desarrollo de la arquitectura en función del mercado; analizar cómo los lenguajes y estéticas propias del marketing inmobiliario refuerzan narrativas aspiracionales hegemónicas; explorar las conexiones emocionales orgánicas en una vivienda construida en función de sus habitantes; y desnormalizar la tendencia hacia la reducción y estandarización de viviendas en Lima Metropolitana. Los materiales utilizados incluyen hilo y papel vegetal, mientras que los métodos abarcan el dibujo con costura a máquina sobre papel y la comparación de casos de estudio. Como guía de la investigación, se plantea la siguiente pregunta: ¿nuestra forma de vivir determina la arquitectura o la arquitectura determina nuestra forma de vivir?.
¡Move in now!
Keywords: Neoliberal architecture; Self-built housing; Inhabitants; Sewing; Drawing; Arquitectura neoliberal; Autoconstrucción; Habitantes; Costura; Dibujo; https://purl.org/pe-repo/ocde/ford#6.04.01